Comprehensibility and acceptability of deviant forms of formulaic expressions in English of Filipino graduate students - Tan, Perla M. 1948- (1982)
The study examined the deviants produced by adult Filipino speakers in the use of formulaic expressions in English and determined the levels of comprehensibility and acceptability of these errors to various groups of English speakers. Result of the study is hoped to provide insights into the development of English as a second language in the Philippines and the extent by which Filipino English facilitate communication within and outside the nation. It can also serve as guide to outsiders seeking cross-cultural interrelationships and making contact through the acceptable means of communication. Deviants of formulaic expressions in English provide the enthusiastic language learners the opportunity to analyze the linguistic peculiarities of the local language influencing the formation of deviants.
Thesis (Ph.D.)--University of the Philippines, Quezon City.
Keywords: English language -- Philippines